Artificial Intelligence in the Perspective of Students in BIPA (Bahasa Indonesia for Foreign Speakers) Learning - Sohnui, Suhailee; Mukhlis, Muhammad; Pendri, Apri (UIR Press, 2025)
This study aims to explore the use of Artificial Intelligence (AI) in the teaching of Bahasa Indonesia for Foreign Speakers (BIPA) and its impact on the learning experience of foreign students. BIPA faces significant challenges due to the structural differences between Bahasa Indonesia and other foreign languages, as well as the limitations of traditional teaching methods. AI technology offers the potential to enhance the learning experience by providing speaking exercises, pronunciation practice, and real-time feedback tailored to students' abilities. This research uses a qualitative phenomenological approach, with in-depth interviews and observations as the data collection methods. The subjects of the study consist of 30 foreign students who have used AI-based applications in BIPA learning for at least three months. The collected data is analyzed using thematic analysis techniques to identify key themes related to the students' experiences with AI technology. The results of the study show that most students reported improvements in their language skills, especially in vocabulary, grammar understanding, and pronunciation, after using AI applications. As many as 85% of students felt more engaged in learning with AI, as the application provided immediate feedback and allowed them to learn independently. However, there were also some technical challenges faced by students, such as issues with internet connectivity and application errors, as well as limitations in understanding cultural contexts and more complex conversations. Nevertheless, students generally felt that AI provided a more flexible and efficient learning experience compared to traditional teaching methods. This study contributes to the development of BIPA teaching by utilizing AI as a supplementary technology. The findings also highlight the importance of further development in improving the technical stability and the AI's ability to understand Indonesia's cultural context to create a more comprehensive learning experience.